Black phosphorus saturable absorber for Q-switched Er:YAG laser at 1645 nm. (1st March 2018) - Guo, Lei; Li, Tao; Zhang, Shuaiyi; Wang, Mingjian; Yang, Kejian; Fan, Mingqi; Zhao, Shengzhi; Li, Ming
Highlights: The BP saturable absorber (SA) was prepared by liquid phase exfoliation method. Saturable absorption properties of BP-SAs were characterized at 1.6 μm. Inband pumped Q-switched Er:YAG laser at 1645 nm was demonstrated with BP-SAs. Abstract: A Q-switched Er:YAG solid-state laser at 1645 nm based on black phosphorus (BP) saturable absorbers (SAs) was demonstrated firstly to our knowledge. The BP-SA was fabricated by drop-casting BP nanoplatelets dispersion on a YAG substrate and corresponding saturable absorption properties were characterized at 1.6 μm. By employing as-prepared BP-SAs, stable Q-switched laser operations were achieved with a pulse width of 2.8 μs and a repetition rate of 34 kHz, corresponding to the average output power of 0.33 W. The results verify that BP-SAs have great potential for pulsed 1.6 μm lasers.